2019
DOI: 10.3390/nu12010051
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin and Mineral Supplementation Practices in Preterm Infants: A Survey of Australian and New Zealand Neonatal Intensive and Special Care Units

Abstract: Preterm infants are at increased risk of micronutrient deficiencies as a result of low body stores, maternal deficiencies, and inadequate supplementations. The aim of this survey was to investigate current vitamin and mineral supplementation practices and compare these with published recommendations and available evidence on dosages and long-term outcomes of supplementations in preterm infants. In 2018, a two-part electronic survey was emailed to 50 Australasian Neonatal Dietitians Network (ANDiN) member and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Eleven articles met the selection criteria, and were included in this review. Of the nine excluded articles, two were discussion papers [ 23 , 24 ], two reported international studies without data specific to New Zealand [ 25 , 26 ], two reported outcomes irrelevant to this review [ 27 , 28 ], and the remaining three were a review [ 29 ], a commentary [ 30 ], and a letter [ 31 ]. Figure 1 displays the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles met the selection criteria, and were included in this review. Of the nine excluded articles, two were discussion papers [ 23 , 24 ], two reported international studies without data specific to New Zealand [ 25 , 26 ], two reported outcomes irrelevant to this review [ 27 , 28 ], and the remaining three were a review [ 29 ], a commentary [ 30 ], and a letter [ 31 ]. Figure 1 displays the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Survey results discussing variations in vitamin supplementation regimens ( 44 ), dietetic resourcing and written nutrition policies ( 45 ) have been reported elsewhere.…”
Section: Part 2–site-specific Nutrition Practicesmentioning
confidence: 99%
“…Even in cases of iron supplementation, brain alterations can be irreversible, especially when iron deficiency is present during phases of neurogenesis and cellular differentiation of the brain areas [32]. Studies also show that in situations of iron deficiency (without gestational anemia), damages can occur to the cellular processes of white cells and in regions of gray matter of the central nervous system, which persist in adult life [31,106].…”
Section: Ironmentioning
confidence: 99%
“…Newborns can also receive iron supplementation, but this should be followed on an individual basis; thus, dosages and duration of administration will vary according to the birth weight [106]. Supplementation occurs in specific situations, as the newborn is able to meet iron needs by recycling hemoglobin since breast milk offers a lower iron content [107].…”
Section: Ironmentioning
confidence: 99%